Development and implementation of a fuzzy logic controller for a high performance battery charging system using microcontroller - Ahmad Rasyidi, Abd Razak (2013)
Nowadays the application of the battery is very useful and renewable battery has variety function and application in the industry. It is not only use in the automotive industry; it also uses in the telecommunication, medicine, technology and many more. The most important application in the biggest industry is as the storage energy. In this part, the renewable battery serves as the backup energy source for critical electricity needs, such as in solar, wind and hydraulic energies system. The process of the charging battery is depends on its chemical composition, capability, capacity and its architecture construction. This intelligent battery charger will control the algorithm implementation with the fuzzy logic. The intelligent digital architecture is implementation with microcontroller. This microcontroller comes with the specialized instruction for fuzzy logic programming. The external analogue to digital converter is implemented in this project for measures the current and the voltage to achieve high resolution.